2017
DOI: 10.1111/iej.12850
|View full text |Cite
|
Sign up to set email alerts
|

Moisture content of root canal dentine affects detection of microcracks using micro‐computed tomography

Abstract: Moisture content of dentine influenced detection of microcracks when evaluated using micro-CT. Scanning should be performed on dried specimens to allow reliable identification of dentinal defects. Formation of new cracks during dry periods up to 24 h was disproved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
0
30
2
Order By: Relevance
“…The topic remains controversial, especially as cracks can appear or disappear as a function of moisture content of the dentine due to swelling of the collagen (Rödig et al . ). Nevertheless, Atmeh & Watson () reported dentine distortion and crack propagation by examining tooth‐cutting interactions using video‐rate confocal microscopy and each intracanal mechanical manipulation seems to cause root surface strain (Pilo et al .…”
Section: Introductionmentioning
confidence: 97%
“…The topic remains controversial, especially as cracks can appear or disappear as a function of moisture content of the dentine due to swelling of the collagen (Rödig et al . ). Nevertheless, Atmeh & Watson () reported dentine distortion and crack propagation by examining tooth‐cutting interactions using video‐rate confocal microscopy and each intracanal mechanical manipulation seems to cause root surface strain (Pilo et al .…”
Section: Introductionmentioning
confidence: 97%
“…Moisture content of dentine can in uence the detection of micro-CT. So in this study, we performed dried condition to avoid the missing of some cracks (22). Also, in order to reduce the omission diagnostic rate of dentin cracks, we used micro-CT to detect tooth cracks which reached or exceeded the enamel-dentinal junction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the length of microcracks significantly increased after the instrumentation of mandibular molars with a rotary single‐file system (OneShape) compared with reciprocating systems (Reciproc, WaveOne) . The use of different scan and reconstruction parameters, different micro‐CT resolutions or different moisture conditions of root dentin influencing the visibility of microcracks may have caused these conflicting findings.…”
Section: Discussionmentioning
confidence: 99%
“…This technique allows three‐dimensional, noninvasive assessment and visualisation of microcracks and facilitates pre‐ and post‐operative analysis of the same specimens which serve as their own control . In this study, specimens were scanned after 2 h dry time as it was demonstrated that the moisture condition of dentin influences the visibility of microcracks on micro‐CT images and scanning of wet samples may lead to false‐negative results and underestimation of dentinal crack formation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation